Sampling and its impact on results and interpretation of analysis - Kuzinska, Vladyslava; Ishchenko, Vera (My University, 2022)
The research used the analysis of modern domestic and foreign scientific literature, the instructions of the American Society for Testing and Materials (ASTM), the International Association of Official Analytical Chemists (OAAC International), state DSTU for sampling solids and liquids. The importance of the sample preparation stage in chemical analysis is noted. In particular, if the samples are taken incorrectly, even if they are properly stored, prepared and analyzed, the researcher will still get false results. However, with the necessary experience and the use of statistical methods, sampling can be performed with the same accuracy as the analysis itself. The peculiarity of sample preparation of solid-phase and liquid samples is considered.

У дослідженні використано аналіз сучасної вітчизняної та закордонної наукової літератури, інструкції Американської спільноти по тестуванню та матеріалам (ASTM), Міжнародної асоціації офіційних хіміків-аналітиків (OAAC International), державні ДСТУ на відбір проб твердих речовин та рідин. Відмічається важливість етапу пробопідготовки в хімічному аналізі. Зокрема, якщо проби відібрані неправильно, то у випадку навіть правильного їх зберігання, підготовки та самого аналізу дослідник все рівно отримає хибні результати. Проте при наявності необхідного досвіду та використанні статистичних методів пробовідбір можна виконати з тією ж точністю, що й сам аналіз. Розглянуто особливість пробопідготовки твердофазових та рідинних зразків.
Keywords: кафедра харчової хімії; sampling; solid phase; liquid samples; пробовідбір; тверда фаза; рідкі проби